Transcriptome analysis reveals the regulation of cyclic nucleotide-gated ion channels in response to exogenous abscisic acid and calcium treatment under drought stress in tomato - Shi, Jinyan; Du, Xiangge (Frontiers in Genetics, 2023)
Drought stress can limit the growth and development of tomato seedlings and cause considerable loss of tomato yield. Exogenous abscisic acid (ABA) and Ca2+ can effectively alleviate the damage of drought stress to plants in part because Ca2+ acts as a second messenger in the drought resistance pathway. Although cyclic nucleotide-gated ion channels (CNGCs) are common non-specific Ca2+ osmotic channels in cell membranes, a thorough understanding of the transcriptome characteristics of tomato treated with exogenous ABA and Ca2+ under drought stress is necessary to characterize the molecular mechanism of CNGC involved in tomato drought resistance. There were 12,896 differentially expressed genes in tomato under drought stress, as well as 11,406 and 12,502 differentially expressed genes after exogenous ABA and Ca2+ application, respectively. According to functional annotations and reports, the 19 SlCNGC genes related to Ca2+ ion transport were initially screened, with 11 SlCNGC genes that were upregulated under drought stress and downregulated after exogenous ABA application. After exogenous Ca2+ application, the data showed that two of these genes were upregulated, while nine genes were downregulated. Based on these expression patterns, we predicted the role of SlCNGC genes in the drought resistance pathway and their regulation by exogenous ABA and Ca2+ in tomato. The results of this study provide foundational data for further study of the function of SlCNGC genes and a more comprehensive understanding of drought resistance mechanisms in tomato.